b) \(\dfrac{3}{4}+\dfrac{1}{4}:x=\dfrac{2}{5}\)
\(\Rightarrow\dfrac{1}{4}:x=\dfrac{2}{5}-\dfrac{2}{4}\)
\(\Rightarrow\dfrac{1}{4}:x=-\dfrac{1}{10}\)
\(\Rightarrow x=\dfrac{1}{4}:\left(-\dfrac{1}{10}\right)\)
\(\Rightarrow x=-\dfrac{3}{2}\)
b) \(\dfrac{3}{4}+\dfrac{1}{4}:x=\dfrac{2}{5}\)
\(\Rightarrow\dfrac{1}{4}:x=\dfrac{2}{5}-\dfrac{2}{4}\)
\(\Rightarrow\dfrac{1}{4}:x=-\dfrac{1}{10}\)
\(\Rightarrow x=\dfrac{1}{4}:\left(-\dfrac{1}{10}\right)\)
\(\Rightarrow x=-\dfrac{3}{2}\)
1.Tìm x
a) \(1\dfrac{4}{5}=-0,15-x\)
b) \(-\dfrac{4}{7}-x=\dfrac{3}{5}-2x\)
c) \(\left(\dfrac{3}{8}-\dfrac{1}{5}\right)+\left(\dfrac{5}{8}-x\right)=\dfrac{1}{5}\)
B= 0,25 +3/5 - (1/8-2/5+\(1\dfrac{1}{4}\) )
C=\(\dfrac{2}{3}-\left(\dfrac{-1}{4}\right)+\dfrac{3}{5}-\dfrac{7}{45}-\left(\dfrac{-5}{9}\right)+\dfrac{1}{12}+\dfrac{1}{35}\)
D=\(\left(5-\dfrac{3}{4}+\dfrac{1}{5}\right)-\left(6+\dfrac{7}{4}-\dfrac{8}{5}\right)-\left(2-\dfrac{5}{7}+\dfrac{16}{5}\right)\)
e) \(\dfrac{3}{3x}-\dfrac{3}{12}=\dfrac{4}{5}-\left(\dfrac{7}{x}-2\right)\)
f) \(\dfrac{1}{x-1}+\dfrac{-2}{3}\left(\dfrac{3}{4}-\dfrac{6}{5}\right)=\dfrac{5}{2-2x}\)
g) \(3-\dfrac{2}{2x-3}=\dfrac{2}{5}=\dfrac{2}{9-6x}-\dfrac{3}{2}\)
h) \(\dfrac{x}{2}-\dfrac{1}{x}=\dfrac{1}{12}\)
i) \(x^2-\dfrac{7}{6}x+\dfrac{1}{3}=0\)
k) \(\dfrac{13}{x-1}+\dfrac{5}{2x-2}-\dfrac{6}{3x-3}\)
m) \(\left(\dfrac{3}{2}-\dfrac{2}{-5}\right):x-\dfrac{1}{2}=\dfrac{3}{2}\)
n) \(\left(\dfrac{3}{2}-\dfrac{5}{11}-\dfrac{3}{13}\right)\left(2x-2\right)=\left(-\dfrac{3}{4}+\dfrac{5}{22}+\dfrac{3}{26}\right)\)
Thực hiện phép tính
a. \(\dfrac{-1}{24}-\left\{\dfrac{1}{4}-\left(\dfrac{1}{2}-\dfrac{7}{8}\right)\right\}\)
b.\(\left(8\dfrac{5}{11}+3\dfrac{5}{8}\right)-3\dfrac{5}{11}\)
c.\(\dfrac{4}{9}:\left(\dfrac{-1}{7}\right)+6\dfrac{5}{9}:\left(\dfrac{-1}{7}\right)\)
d. \(\left(\dfrac{-1}{5}+\dfrac{3}{7}\right):\dfrac{2}{11}+\left(\dfrac{-4}{5}+\dfrac{4}{7}\right):\dfrac{2}{11}\)
M.n giúp mk nha
c )\(\dfrac{x}{2}-\left(\dfrac{3x}{5}-\dfrac{13}{5}\right)=-\left(\dfrac{7}{5}+\dfrac{7}{10}.x\right)\)
d)\(\dfrac{2x-3}{3}+\dfrac{-3}{2}=\dfrac{5-3x}{6}-\dfrac{1}{3}\)
Tính hợp lý:
a, \(\dfrac{-3}{4}.5\dfrac{3}{13}-0,75.\dfrac{36}{13}\)
b, \(4\dfrac{5}{9}:\left(\dfrac{-5}{7}\right)+\dfrac{49}{9}:\left(\dfrac{-5}{7}\right)\)
c, \(\left(\dfrac{-3}{5}+\dfrac{4}{9}\right):\dfrac{7}{11}+\left(\dfrac{-2}{5}+\dfrac{5}{9}\right):\dfrac{7}{11}\)
d, \(\dfrac{6}{7}:\left(\dfrac{3}{26}-\dfrac{3}{13}\right)+\dfrac{6}{7}:\left(\dfrac{1}{10}-\dfrac{8}{5}\right)\)
a)\(\dfrac{-12}{15}+\dfrac{-4}{26}\) b)\(5\dfrac{1}{3}-2\dfrac{4}{5}\)
c)\(\dfrac{4}{5}-\left(-\dfrac{2}{7}\right)+-\dfrac{5}{10}\) d)\(-1\dfrac{2}{7}+\dfrac{3}{14}-\dfrac{5}{21}\)
e)\(12-\dfrac{11}{121}+\left(-\dfrac{8}{9}\right)-\left(-\dfrac{3}{7}\right)\) f) \(\dfrac{11}{12}-\left(1\dfrac{3}{4}\right)-\dfrac{2}{16}\)
Bài 8:
b)\(\left(\dfrac{-4}{3}\right)+\left(\dfrac{-2}{5}\right)+\left(\dfrac{-3}{2}\right)\)
c) \(\dfrac{4}{5}-\left(\dfrac{-2}{7}\right)-\dfrac{-7}{10}\)
d) \(\dfrac{2}{3}-\left[\left(\dfrac{-7}{4}\right)-\left(\dfrac{1}{2}+\dfrac{3}{8}\right)\right]\)